Defesa do domínio pessoal e resolução de conflitos familiares por adolescentes - Costa, Lívia Braga de Sá (2017)
This study aims at verifying how teenage children defend their Personal Domain (PD) when confronted with the use of parental authority from different hypothetical situations. We used Larry Nucci’s approach on Personal Domain. According to the author, Personal Domain corresponds to a domain of the social cognition that encompasses behaviors regarding the individual himself, the strictly personal rules e that can be found outside the social justifiable regulation area. To pursue this goal, were interviewed 36 adolescents, students from private schools, divided equally regarding their gender. In the interview, the participants were introduced to four dilemmas concerning The First steps of Sexual Life, Career Choice, Privacy and Curfew. To analyze the data, we used non parametric tests and a semantic content analysis. From the results, four categories of Personal Domain were attested. For each of the categories, a defense level was attributed: Absence of PD defense, level 0, in which adolescents do not defend their PD because they consider themselves incapable of managing their own lives; Inconsistent PD defense, level 1, which is hierarchically superior to level 0, however, displays a low level of PD defense, since it shows a conflict between their rights and their parents’ rights; Prudent PD defense, level 2, which indicates a level above the aforementioned one because it encompasses answers that involve the understanding of the adolescent of their parents concern in protecting them; Total PD defense, level 3, that was considered the highest one, since its answers show that the children recognize their privacy zone and defend it regardless of their parent’ expectations. The results of non parametric tests showed that the most prevailing answer to the dilemmas concerning the First steps of Sexual Life, Career Choice and Privacy was the level 3. The only exception was concerning the Curfew, in which most answers were in accordance to level 2. We believe this exception is due to the specificity of the content of this dilemma, since staying out at night, not respecting the Curfew, can represent a threaten to the adolescent’s safety. Concerning conflict resolution, we observed that: Dialogue/Explanation had the highest frequency of answers in all dilemmas, which may indicate that adolescents found a democratic way of solving conflicts; Submission and Guilt assumption were significantly associated with levels 0 and 1 of PD defense, which suggests that these psychological aspects prevent an efficient PD defense; Negotiation, in turn, was associated with level 1, which indicates that even though this resolution strategy serves to a more harmonious family environment, it may not be such an efficient strategy for the adolescent’s autonomy defense.